Milan Hlavsa a peripetie existence skupiny Plastic People of the Universe: Životní příběh a diskurs - Pecková, Barbora (Lidé města, 2017)
The paper interprets the life story of the musician and the co-founder of the group “The Plastic People of the Universe”, Milan Hlavsa, through the analysis of interviews realized with Hlavsa in the years 1986–1991. The interpretation focuses on the roots of his relationship to rock ’n’ roll music, of his efforts to be a professional musician, of his relationship to Ivan Jirous, and of his experiences with communist repression. The case study of Hlavsa’s life story embeds the topic of the identification of rock ’n’ roll youth subculture in the underground culture. The oral history and biographical method used in the analysis shows the disproportion of the self-identification of the individual and the discourses built around the underground community. The paper discusses two of the most influential publications about the underground: Miroslav Vaněk’s Byl to jenom Rock’n’ roll (It Was Just Rock ’n’ roll) and Jonathan Bolton’s Worlds of Dissent: Charter 77, The Plastic People of the Universe, and Czech Culture under Communism. It points out how the methodology and selection of historical subjects and sources influences the interpretation of the phenomenon of the underground and its participants.